Pure copper plate

By controlling the content of trace impurity elements in pure copper plates, using these elements to suppress grain growth in the grain boundaries, the problem of coarse grains of copper materials at high temperatures is solved, and the high temperature stability and thermal processing properties of the material are achieved.

CN115896532BActive Publication Date: 2025-05-02MITSUBISHI MATERIALS CORP
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202211648894.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-03-29
Filing Date
2019-12-11
Publication Date
2025-05-02
Estimated Expiration
2039-12-11

AI Technical Summary

Technical Problem

In electrical/electronic parts such as radiators or thick copper circuits, when the ceramic substrate is bonded to the copper plate, high temperature may cause the grains of the copper material to be coarser, affecting the appearance and performance of the material.

Method used

By controlling the content of trace impurity elements, especially the content of P, Pb, Se, Te and S in the pure copper plate, these elements are used to suppress the growth of grains in the grain boundary, thereby preventing grain coarseness and unevenness after heating.

Benefits of technology

It can suppress the coarseness and unevenness of grains under high temperature conditions, maintain excellent thermal processing properties of the material, and is suitable for electrical/electronic parts for high current purposes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004007717150000131
    Figure BDA0004007717150000131
  • Figure BDA0004007717150000141
    Figure BDA0004007717150000141
  • Figure BDA0004007717150000151
    Figure BDA0004007717150000151
Patent Text Reader

Abstract

The present invention provides a pure copper plate. The pure copper plate of the present invention has a Cu purity of 99.96 mass % or more, the remainder being inevitable impurities, a P content of 2 mass ppm or less, and a total content of Pb, Se and Te of 10 mass ppm or less. The S content may be 2 mass ppm or more and 20 mass ppm or less.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is a divisional application for the invention patent application with application date of December 11, 2019, application number 201980072918.8, and invention name “Pure Copper Plate”. Technical Field

[0002] The present invention relates to a pure copper plate suitable for electrical / electronic parts (electrical parts or electronic parts) such as a radiator or a thick copper circuit (a circuit with a thick copper pattern), and more particularly to a pure copper plate capable of suppressing grain coarsening during heating.

[0003] This application claims priority based on Patent Application No. 2018-233347 filed in Japan on December 13, 2018 and Patent Application No. 2019-068304 filed in Japan on March 29, 2019, and the contents of which are incorporated herein by reference. Background Art

[0004] Conventionally, copper or copper alloys with high conductivity have been used in electrical and electronic parts such as heat sinks and thick copper circuits.

[0005] Recently, as electronic devices and electric equipment are subjected to higher currents, electric / electronic components used in these electronic devices and electric equipment are required to be larger and thicker in order to reduce current density and diffuse heat generated by modules.

[0006] Here, in semiconductor devices, for example, an insulating circuit substrate in which a copper material is bonded to a ceramic substrate to form the above-mentioned heat sink or thick copper circuit is used.

[0007] When a ceramic substrate is bonded to a copper plate, the bonding temperature is usually set to 800°C or higher, which may cause the grains of the copper material constituting the heat sink or thick copper circuit to coarsen during bonding. In particular, in a copper material composed of pure copper, which has excellent electrical conductivity and heat dissipation, the grains tend to coarsen easily.

[0008] When the grains in a heat sink or thick copper circuit after bonding are coarsened, the coarsening of the grains may cause problems in appearance.

[0009] Here, for example, Patent Document 1 proposes a pure copper material in which grain growth is suppressed.

[0010] Patent Document 1 states that by containing S in an amount of 0.0006 to 0.0015 wt %, even when heat treatment is performed at a temperature higher than the recrystallization temperature, the grain size can be adjusted to a certain value.

[0011] However, although Patent Document 1 specifies the S content to suppress grain coarsening, depending on the heat treatment conditions, simply specifying the S content may not be enough to achieve a sufficient effect of suppressing grain coarsening. In addition, after heating, grains may partially coarsen and the crystal structure may be non-uniform.

[0012] Furthermore, when the S content is increased in order to suppress the coarsening of crystal grains, there is a problem that the hot workability is greatly reduced, and the production yield of the pure copper material is greatly reduced.

[0013] Patent Document 1: Japanese Patent Application Laid-Open No. 06-002058 Summary of the invention

[0014] The present invention has been made in view of the above circumstances, and an object of the present invention is to provide a pure copper plate which has excellent hot workability and can suppress coarsening and non-uniformity of crystal grains even after heating.

[0015] In order to solve this problem, the inventors of the present invention have conducted in-depth research and obtained the following insights: Among the impurity elements contained in a trace amount in a pure copper plate, there is an element that has the effect of inhibiting grain coarsening (the effect of inhibiting grain growth) by existing at the grain boundary. Therefore, by making use of this element that has the effect of inhibiting grain growth (hereinafter referred to as the element that inhibits grain growth (grain growth inhibiting element)), it is possible to inhibit the coarsening and homogenization of grains even after heating. In addition, the inventors of the present invention have obtained the following insights: In order to make the grain growth inhibiting element fully act, it is effective to limit the content of a specific element.

[0016] In addition, the effect of suppressing the growth of crystal grains is also referred to as a crystal growth suppressing effect, and the effect of suppressing the coarsening of crystal grains is also referred to as a crystal grain coarsening suppressing effect.

[0017] The present invention is completed based on the above-mentioned insights. A pure copper plate of one embodiment of the present invention is characterized in that the Cu purity is 99.96 mass % or more, the remainder is unavoidable impurities, the P content is 2 mass ppm or less, and the total content of Pb, Se and Te is 10 mass ppm or less.

[0018] According to the pure copper plate of this configuration, since the P content is set to 2 mass ppm or less, the effect of the grain growth suppressing element present in trace amounts at the grain boundaries can be suppressed from being inhibited by P segregating at the grain boundaries, and the coarsening and inhomogenization of the grains can be suppressed even after heating.

[0019] Furthermore, the solid solution limit of Pb, Se and Te in Cu is low, which is equivalent to a grain growth inhibitory element that suppresses grain coarsening by segregating at the grain boundary. Therefore, although Pb, Se and Te can be contained in trace amounts, these elements also have the effect of greatly reducing hot workability. Therefore, by limiting the total content of Pb, Se and Te to less than 10 mass ppm, especially by setting the Pb content to less than 3 mass ppm, hot workability can be ensured.

[0020] Here, in the pure copper plate according to one aspect of the present invention, the S content is preferably in the range of 2 mass ppm or more and 20 mass ppm or less.

[0021] In this case, by containing 2 mass ppm or more of S, which corresponds to the above-mentioned grain growth inhibiting element, it is possible to reliably suppress the coarsening and inhomogeneity of the grains even after heating. In addition, by limiting the S content to 20 mass ppm or less, hot workability can be sufficiently ensured.

[0022] Furthermore, in the pure copper plate according to one aspect of the present invention, the total content of Mg, Sr, Ba, Ti, Zr, Hf, and Y is preferably 10 mass ppm or less.

[0023] Elements such as Mg, Sr, Ba, Ti, Zr, Hf, and Y that may be contained as unavoidable impurities may form compounds with S, Se, Te, Pb, etc., which are grain growth inhibitory elements, and thus may hinder the effects of these grain growth inhibitory elements. Therefore, by limiting the total content of these Mg, Sr, Ba, Ti, Zr, Hf, and Y to 10 mass ppm or less, the grain growth inhibitory effect of the grain growth inhibitory elements can be fully exerted, and even after heating, the coarsening and inhomogeneity of the grains can be reliably suppressed.

[0024] In the pure copper plate according to one aspect of the present invention, the grain size of the crystal grains on the rolled surface is preferably 10 μm or more.

[0025] In this case, since the grain size of the crystal grains on the rolled surface is set to 10 μm or more, when the pure copper plate is heated at 800° C. or more, the coarsening of the crystal grains is promoted and the structural inhomogeneity can be suppressed.

[0026] In addition, the particle size of the crystal grains is also called the crystal grain size.

[0027] Furthermore, in the pure copper plate according to one aspect of the present invention, the aspect ratio of the crystal grains on the rolled surface is preferably 2 or less.

[0028] In this case, since the aspect ratio of the crystal grains of the rolled surface is set to less than 2, the degree of processing is low and large strains will not be accumulated. That is, the dislocation density is relatively low. Therefore, the driving force of recrystallization due to the dislocation density decreases, and the coarsening of the crystal grains after heating can be further suppressed. The value of the aspect ratio here is the value of the major diameter divided by the minor diameter, i.e., represented by the major diameter / minor diameter.

[0029] Furthermore, in the pure copper plate according to one aspect of the present invention, the grain size after heat treatment at 800° C. for 1 hour is preferably within a range of 100 μm to 300 μm.

[0030] In this case, since the grain size after the heat treatment at 800° C. for 1 hour is set within the range of 100 μm to 300 μm, the coarsening of the grains can be reliably suppressed even after heating.

[0031] In the pure copper plate according to one aspect of the present invention, the crystal grain size after being heated at 800° C. or higher and bonded to the ceramic substrate is preferably within a range of 100 μm to 300 μm.

[0032] In addition, in the pure copper plate of one embodiment of the present invention, the maximum crystal grain size d in the range of 50 mm×50 mm after heat treatment at 800° C. for 1 hour is max The average crystal grain size d ave The ratio d max / d ave Preferably, it is 10 or less.

[0033] In this case, the maximum grain size d after heat treatment at 800°C for 1 hour is max The average crystal grain size d ave The ratio d max / d ave By setting the ratio to 10 or less, it is possible to reliably suppress the crystal grains from becoming non-uniform even after heating.

[0034] In addition, in the pure copper plate according to one aspect of the present invention, the tensile strength is preferably 500 MPa or less.

[0035] In this case, since the tensile strength is 500 MPa or less and the properties as a pure copper plate are ensured, it is particularly suitable as a base material for electric and electronic parts for large current use.

[0036] According to one aspect of the present invention, it is possible to provide a pure copper plate which has excellent hot workability and can suppress coarsening and non-uniformity of crystal grains even after heating. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 This is a flowchart of the method for producing a pure copper plate according to the present embodiment. DETAILED DESCRIPTION

[0038] A pure copper plate according to one embodiment of the present invention will be described below.

[0039] The pure copper plate of this embodiment can be used as a base material for electrical / electronic parts such as heat sinks and thick copper circuits. When forming (molding) the aforementioned electrical / electronic parts, the pure copper plate is heated at 800° C. or higher and bonded to a ceramic substrate for use.

[0040] In the pure copper plate of the present embodiment, the Cu purity is 99.96 mass % or more, the remainder is inevitable impurities, the P content is 2 mass ppm or less, and the total content of Pb, Se and Te is 10 mass ppm or less.

[0041] Furthermore, in the pure copper plate of the present embodiment, the S content is preferably in the range of 2 mass ppm or more and 20 mass ppm or less.

[0042] Furthermore, in the pure copper plate of the present embodiment, the total content of Mg, Sr, Ba, Ti, Zr, Hf, and Y as inevitable impurities is preferably 10 mass ppm or less.

[0043] That is, the composition of the pure copper plate can also be described as follows.

[0044] The pure copper plate contains 99.96% by mass or more of Cu and 2% by mass or less of P, and further contains one or more elements selected from Pb, Se and Te with a total content of 10% by mass or less, and the remainder is unavoidable impurities. The pure copper plate further preferably contains 2% by mass or more and 20% by mass or less of S. The pure copper plate further preferably contains one or more selected from Mg, Sr, Ba, Ti, Zr, Hf and Y, and the total amount thereof is 10% by mass or less.

[0045] Regarding the elements other than Cu, when they are contained as inevitable impurities or when they are intentionally contained, the contents of these elements are all within the above ranges. In addition, elements other than Cu can also be referred to as inevitable impurities. The remaining inevitable impurities can also be referred to as elements other than the above-mentioned specific elements.

[0046] Furthermore, in the pure copper plate of the present embodiment, the grain size of the crystal grains on the rolled surface is preferably 10 μm or more.

[0047] Furthermore, in the pure copper plate of the present embodiment, the aspect ratio of the crystal grains on the rolled surface is preferably 2 or less.

[0048] Furthermore, in the pure copper plate of the present embodiment, the grain size after heat treatment at 800° C. for 1 hour is preferably within a range of 100 μm to 300 μm.

[0049] In the pure copper plate of the present embodiment, the crystal grain size after being heated at 800° C. or higher and bonded to the ceramic substrate is preferably within a range of 100 μm to 300 μm.

[0050] In addition, in the pure copper plate of the present embodiment, the maximum crystal grain size d in the range of 50 mm×50 mm after heat treatment at 800° C. for 1 hour is max The average crystal grain size d ave The ratio d max / d ave Preferably, it is 10 or less.

[0051] In addition, in the pure copper plate of the present embodiment, the tensile strength is preferably 500 MPa or less.

[0052] Grain size, grain aspect ratio, grain size after heat treatment, and maximum grain size d after heat treatment max The average crystal grain size d ave This is a value measured by the evaluation method described in the examples described later.

[0053] Here, the reasons why the component composition and various characteristics are specified as described above in the pure copper plate of the present embodiment will be described below.

[0054] (Cu purity: 99.96 mass % or more)

[0055] Electric and electronic parts for large current applications are required to have excellent electrical conductivity and heat dissipation in order to suppress heat generation when current is supplied, and pure copper, which has particularly excellent electrical conductivity and heat dissipation, is preferably used.

[0056] Therefore, in the pure copper plate of the present embodiment, the Cu purity is set to 99.96 mass % or more.

[0057] In addition, the Cu purity is preferably 99.965 mass % or more, more preferably 99.97 mass % or more. In addition, the upper limit of the Cu purity is not particularly limited, but when the Cu purity exceeds 99.999 mass %, a special refining process is required, which greatly increases the manufacturing cost, so it is preferably below 99.999 mass %.

[0058] (P content: 2 mass ppm or less)

[0059] P contained as an inevitable impurity is widely used as an element that makes oxygen in copper harmless. However, when P is contained above a certain level (above a specific amount), it not only inhibits oxygen but also inhibits the action of grain growth inhibiting elements present in the grain boundaries. Therefore, when heated to a high temperature, the grain growth inhibiting elements cannot fully function, and may cause coarsening and inhomogeneity of the grains.

[0060] Therefore, in the present embodiment, the P content is limited to 2 mass ppm or less.

[0061] Furthermore, the P content is preferably 1.5 mass ppm or less, and more preferably 1 mass ppm or less. When the P content is less than 0.001 mass ppm, the cost will only be higher. Therefore, the P content is preferably 0.001 mass ppm or more, more preferably 0.005 ppm or more, and even more preferably 0.01 mass ppm or more.

[0062] (Total content of Pb, Se and Te: 10 mass ppm or less)

[0063] Pb, Se, and Te are elements that have low solubility limits in Cu, segregate at grain boundaries, and thus have a function of suppressing coarsening of crystal grains, and also significantly reduce hot workability.

[0064] Therefore, in the present embodiment, in order to ensure hot workability, the total content of Pb, Se, and Te is limited to 10 mass ppm or less.

[0065] In addition, in order to further improve the hot workability, the total content of Pb, Se and Te is preferably 9 mass ppm or less, and more preferably 8 mass ppm or less. In particular, for the Pb content, in order to ensure good hot workability, it is preferably 3 mass ppm or less, and more preferably 2.5 mass ppm or less. When the total content of Pb, Se and Te is set to less than 0.01 mass ppm, the inhibitory effect of crystal grain growth becomes smaller and the cost becomes higher. Therefore, the total content of Pb, Se and Te is preferably 0.01 mass ppm or more.

[0066] (S content: 2 mass ppm or more and 20 mass ppm or less)

[0067] S is an element that has a function of suppressing the coarsening of crystal grains by suppressing grain boundary migration, and reduces hot workability.

[0068] Therefore, when the S content in this embodiment is set to 2 mass ppm or more, the grain coarsening suppression effect due to S can be fully exerted, and the grain coarsening can be reliably suppressed even after heating. On the other hand, when the S content is limited to 20 mass ppm or less, hot workability can be ensured.

[0069] The S content is preferably 2.5 mass ppm or more, more preferably 3 mass ppm or more, and is preferably 17.5 mass ppm or less, more preferably 15 mass ppm or less.

[0070] (Total content of Mg, Sr, Ba, Ti, Zr, Hf, and Y: 10 mass ppm or less)

[0071] Mg, Sr, Ba, Ti, Zr, Hf, and Y contained as inevitable impurities will form compounds with grain growth inhibiting elements (S, Se, Te, Pb, etc.) that inhibit the coarsening of grains, and may lead to the effect of hindering the grain growth inhibiting elements.

[0072] Therefore, in order to reliably suppress the coarsening of crystal grains after heating, the total content of Mg, Sr, Ba, Ti, Zr, Hf, and Y is preferably 10 mass ppm or less.

[0073] Furthermore, the total content of Mg, Sr, Ba, Ti, Zr, Hf, and Y is preferably 7.5 mass ppm or less, and more preferably 5 mass ppm or less. When the total content of Mg, Sr, Ba, Ti, Zr, Hf, and Y is set to less than 0.01 mass ppm, the cost will increase. Therefore, the total content of Mg, Sr, Ba, Ti, Zr, Hf, and Y is preferably 0.01 mass ppm or more.

[0074] (Other unavoidable impurities)

[0075] Examples of other inevitable impurities other than the above elements include Ag, B, Bi, Ca, Sc, rare earth elements (excluding Y and Sc), V, Nb, Ta, Cr, Mo, W, Mn, Re, Fe, Ru, Os, Co, Rh, Ir, Ni, Pd, Pt, Au, Zn, Cd, Hg, Al, Ga, In, Ge, Sn, As, Sb, Ti, Be, N, C, Si, Li, H, and O. Since these inevitable impurities may reduce the electrical conductivity, the total amount of these inevitable impurities is preferably set to 0.035% by mass or less.

[0076] (Grain size of rolled surface: 10 μm or more)

[0077] In the pure copper plate of the present embodiment, when the grain size of the rolled surface is fine, recrystallization easily proceeds when the pure copper plate is heated at 800° C. or higher, which may promote the coarsening of the grains and the inhomogeneity of the structure.

[0078] Therefore, in order to further suppress the coarsening of crystal grains, the grain size of the crystal grains on the rolled surface is preferably 10 μm or more.

[0079] In addition, the grain size of the rolled surface is preferably 15 μm or more, more preferably 20 μm or more. The grain size of the rolled surface is more preferably 25 μm or more, further preferably 30 μm or more, and particularly preferably more than 40 μm. When the grain size exceeds 300 μm, the cost becomes high. And the grain size after being kept at 800°C for 1 hour will exceed 300 μm. Therefore, the grain size of the rolled surface is preferably 300 μm or less, more preferably 270 μm or less, and particularly preferably 250 μm or less.

[0080] (Aspect ratio of rolled grains: 2 or less)

[0081] The aspect ratio of the grain is an indicator of the degree of material processing. The higher the aspect ratio, the higher the degree of processing, the higher the dislocation density accumulated in the material, that is, the higher the strain energy. Here, when the strain energy accumulated in the material is high, the driving force for recrystallization becomes higher, and the grains are prone to coarsening during heating.

[0082] Therefore, in order to suppress the coarsening of the grains, the aspect ratio of the grains on the rolled surface is preferably less than 2. The aspect ratio value here is the value obtained by dividing the major diameter calculated by the aspect ratio measurement method of the grains described later by the minor diameter calculated by the measurement method described later, that is, expressed as the average value of major diameter / minor diameter.

[0083] The aspect ratio of the crystal grains on the rolled surface is preferably 1.9 or less, and more preferably 1.8 or less. The substantial lower limit of the aspect ratio of the crystal grains on the rolled surface is 0.5.

[0084] (Grain size after heat treatment at 800°C for 1 hour: 100 μm or more and 300 μm or less)

[0085] In the pure copper plate of this embodiment, when the grain size after heat treatment at 800°C for 1 hour is within the range of 100 μm to 300 μm, the coarsening of the grains can be reliably suppressed even when heated to 800°C, and the plate is particularly suitable as a substrate for a thick copper circuit or heat sink bonded to a ceramic substrate.

[0086] Furthermore, the grain size after heat treatment at 800°C for 1 hour is preferably 110 μm or more, more preferably 120 μm or more. Furthermore, the grain size after heat treatment at 800°C for 1 hour is preferably 290 μm or less, more preferably 280 μm or less.

[0087] (d after heat treatment at 800℃ for 1 hour max / d ave : 10 or less)

[0088] In the pure copper plate of the present embodiment, the maximum crystal grain size d in the range of 50 mm×50 mm after heat treatment at 800° C. for 1 hour ismax The average crystal grain size d ave The ratio d max / d ave When the ratio is 10 or less, even when heated to 800° C. or higher, the non-uniformity of crystal grains can be reliably suppressed, and the composite is particularly suitable as a base material for a thick copper circuit or a heat sink bonded to a ceramic substrate.

[0089] The maximum grain size d in the range of 50 mm × 50 mm after heat treatment at 800°C for 1 hour is max The average crystal grain size d ave The ratio d max / d ave It is preferably 9 or less, and more preferably 8 or less. The maximum crystal grain size d max The average crystal grain size d ave The ratio d max / d ave It is preferably greater than 1.03, more preferably greater than 1.05.

[0090] (Tensile strength: 500MPa or less)

[0091] In the pure copper plate of the present embodiment, the tensile strength is set to 500 MPa or less, thereby ensuring the characteristics as a pure copper plate, and the pure copper plate is particularly suitable as a base material of electric and electronic parts for large current use.

[0092] The tensile strength of the pure copper plate is preferably 475 MPa or less, more preferably 450 MPa or less, further preferably 400 MPa or less, and particularly preferably 350 MPa or less. The lower limit of the tensile strength of the pure copper plate is not particularly limited, but is preferably 100 MPa or more.

[0093] Next, with respect to the method for manufacturing the pure copper plate of the present embodiment thus constituted, reference is made to Figure 1 The flowchart shown is used for explanation.

[0094] (Melting / Casting Process S01)

[0095] First, a copper raw material purified to a P content of 0.001 mass ppm or less is melted to prepare a copper melt. In addition, as the copper raw material, for example, 4NCu with a purity of 99.99 mass % or more and 5NCu with a purity of 99.999 mass % or more are preferably used.

[0096] When S is added, S alone or a Cu-S master alloy can be used. When a Cu-S master alloy is produced, it is also preferred to use 4NCu having a purity of 99.99 mass % or more and 5NCu having a purity of 99.999 mass % or more.

[0097] Furthermore, in order to reduce the hydrogen concentration in the melting step, the melting is performed in an inert gas atmosphere (such as Ar gas) having a low vapor pressure of H 2 O, and the holding time during the melting is preferably limited to a minimum.

[0098] Then, the copper melt after adjusting the composition is poured into a casting mold to produce an ingot. In addition, in consideration of mass production, it is preferable to use a continuous casting method or a semi-continuous casting method.

[0099] (Hot working process S02)

[0100] Next, heat treatment is performed to homogenize the structure.

[0101] The hot working temperature is not particularly limited, but is preferably within a range of 500°C to 1000°C.

[0102] The total working rate of hot working is preferably 50% or more, more preferably 60% or more, and even more preferably 70% or more.

[0103] Furthermore, the cooling method after hot working is not particularly limited, but air cooling or water cooling is preferred.

[0104] Furthermore, the processing method in the hot working step S02 is not particularly limited, and rolling, extrusion, groove rolling, forging, pressing, etc. can be used. When the final shape is a plate or a strip, rolling is preferably used.

[0105] (Cold working process S03)

[0106] Next, the copper material after the hot working step S02 is cold worked to a specific shape. In addition, the temperature conditions in the cold working step S03 are not particularly limited, but are preferably performed in a range of -200°C to 200°C. In addition, the processing rate in the cold working step S03 is appropriately selected in a manner close to the final shape, but in order to improve productivity, the processing rate is preferably 30% or more.

[0107] Furthermore, the processing method in the cold working step S03 is not particularly limited, and for example, rolling, extrusion, groove rolling, forging, pressing, etc. can be adopted. When the final shape is a plate or a strip, rolling is preferably adopted.

[0108] (Recrystallization Heat Treatment Step S04)

[0109] Next, the copper material after the cold working step S03 is subjected to heat treatment for the purpose of recrystallization. Here, it is preferred that the grain size of the recrystallized grains is 10 μm or more. If the recrystallized grains are fine, then heating at 800° C. or above may promote the coarsening of the grains and the inhomogeneity of the structure.

[0110] The heat treatment conditions of the recrystallization heat treatment step S04 are not particularly limited, but are preferably maintained at a heat treatment temperature in the range of 200° C. to 900° C. for 1 second to 10 hours.

[0111] For example, heat treatment is performed at 350° C. for 6 h (6 hours), heat treatment is performed at 700° C. for 1 h (1 hour), heat treatment is performed at 850° C. for 5 seconds, etc.

[0112] Furthermore, in order to make the recrystallized structure uniform, the cold working step S03 and the recrystallization heat treatment step S04 may be repeated two or more times.

[0113] (Quenching and Tempering Process S05)

[0114] Next, in order to adjust the material strength, the copper material after the recrystallization heat treatment step S04 may be subjected to a tempering process. In addition, if it is not necessary to increase the material strength, the tempering process may not be performed.

[0115] The processing rate of the tempering is not particularly limited, but is preferably carried out within a range of more than 0% and 50% or less in order to adjust the material strength. Furthermore, when the aspect ratio of the grains on the rolled surface is 2.0 or less, the processing rate is preferably limited to 40% or less.

[0116] Furthermore, if necessary, heat treatment may be further performed after the tempering process in order to remove residual strain.

[0117] In this manner, the pure copper plate of this embodiment can be manufactured.

[0118] According to the pure copper plate of the present embodiment configured as above, since the P content is 2 mass ppm or less, P can suppress the effect of inhibiting the grain growth suppressing element present in a trace amount at the grain boundary, and can also suppress the coarsening and non-uniformity of the grains after heating.

[0119] In addition, the solid solution limit of Pb, Se and Te in Cu is low, and the coarsening of grains is suppressed by segregation at the grain boundary. Therefore, since Pb, Se and Te are equivalent to grain growth inhibitory elements, they can also be contained in trace amounts. However, these elements will greatly reduce hot workability. In this way, since Pb, Se and Te are elements that reduce hot workability, hot workability can be ensured by limiting the total content of Pb, Se and Te to less than 10 mass ppm.

[0120] Furthermore, in this embodiment, when the S content is set within the range of 2 mass ppm or more and 20 mass ppm or less, S, which is one of the grain growth suppressing elements, segregates at the grain boundaries, and can reliably suppress the coarsening and inhomogenization of grains during heating. In addition, hot workability can be ensured.

[0121] In addition, in the present embodiment, when the total content of Mg, Sr, Ba, Ti, Zr, Hf, and Y is less than 10 mass ppm, the formation of compounds with grain growth inhibiting elements such as S, Se, Te, and Pb can be suppressed. Thus, the effect of the grain growth inhibiting elements can be fully exerted, and the coarsening and inhomogeneity of the grains during heating can be reliably suppressed.

[0122] In the present embodiment, when the grain size of the crystal grains on the rolled surface is 10 μm or more, when the pure copper plate is heated at 800° C. or more, for example, the recrystallization can be suppressed, and the coarsening of the crystal grains and the inhomogeneity of the structure can be suppressed.

[0123] Furthermore, in the present embodiment, when the aspect ratio of the grains on the rolled surface is 2 or less, the degree of processing is low and large strain is not accumulated, so the driving force for recrystallization becomes small, and the coarsening of the grains after heating can be further suppressed.

[0124] Furthermore, in the present embodiment, when the crystal grain size after heat treatment at 800° C. for 1 hour is within the range of 100 μm to 300 μm, coarsening of the crystal grains can be reliably suppressed even after heating.

[0125] In this embodiment, the maximum grain size d in the range of 50 mm×50 mm after heat treatment at 800° C. for 1 hour is max The average crystal grain size d ave The ratio d max / d ave When it is 10 or less, it is possible to reliably suppress the crystal grains from becoming non-uniform even after heating.

[0126] In addition, in the present embodiment, when the tensile strength is 500 MPa or less, since the characteristics as a pure copper plate are sufficiently ensured, it is suitable as a base material of electric / electronic parts for large current use.

[0127] As mentioned above, although the pure copper plate which concerns on embodiment of this invention is demonstrated, this invention is not limited to this, It can change suitably within the range which does not deviate from the summary of this invention.

[0128] For example, in the above-mentioned embodiment, an example of a method for producing a pure copper plate is described, but the method for producing a pure copper plate is not limited to the method described in the embodiment, and a known production method may be appropriately selected to produce the pure copper plate.

[0129] Example

[0130] Hereinafter, the results of confirmation experiments conducted to confirm the effects of the present invention will be described.

[0131] The P content was purified to less than 0.001 mass ppm by zone melting purification method, and a copper raw material with a purity of 99.999 mass % or more was prepared. The above copper raw material and various elements with a purity of 99 mass % or more (Pb, Se, Te, S, Mg, Sr, Ba, Ti, Zr, Hf, Y) were used to make Cu-1 mass % master alloys of various elements (Cu master alloys containing 1 mass % of various elements).

[0132] By the above method, a copper raw material having a purity of 99.999 mass % or more and a Cu-1 mass % master alloy of various elements were prepared.

[0133] The copper raw material is placed in a high-purity graphite crucible and subjected to high-frequency melting in an atmosphere furnace set to an Ar gas atmosphere. The above-mentioned various elements are added to the obtained copper melt, and the Cu-1 mass% master alloy is prepared to have the composition shown in Tables 1 and 2. In addition, in Tables 1 and 2, the total content of Pb, Se and Te is recorded in the item "Total of 3 elements". And the total content of Mg, Sr, Ba, Ti, Zr, Hf and Y is recorded in the item "Total of 7 elements".

[0134] The obtained copper melt was poured into a heat insulating material casting mold and cooled at a cooling rate of 0.5°C / sec to produce an ingot having a size of about 25 mm in thickness, about 60 mm in width, and about 150 to 200 mm in length.

[0135] The obtained ingot was heated in an Ar gas atmosphere under the temperature conditions shown in Tables 3 and 4 for 1 hour and hot rolled to a thickness of 15 mm.

[0136] The hot-rolled copper material was cut and surface ground to remove the oxide film on the surface. At this time, the thickness of the copper material supplied to the cold rolling was adjusted so that the final thickness would be as shown in Tables 3 and 4, taking into account the rolling reduction rate of the subsequent cold rolling and temper rolling.

[0137] The copper material whose thickness was adjusted as described above was cold rolled under the conditions described in Tables 3 and 4, and then water-cooled.

[0138] Next, the cold-rolled copper material was subjected to recrystallization heat treatment under the conditions described in Tables 3 and 4.

[0139] Next, the copper material after the recrystallization heat treatment was temper-rolled under the conditions shown in Tables 3 and 4, and a strip for property evaluation having a width of 60 mm and a thickness shown in Tables 3 and 4 was produced.

[0140] Next, the following items were evaluated. The evaluation results are shown in Tables 5 and 6.

[0141] (Processability Evaluation)

[0142] As a workability evaluation, the presence or absence of cracks during the hot rolling and cold rolling was observed. Strips with no or almost no cracks observed visually were evaluated as "A". Strips with small cracks less than 1 mm in length were evaluated as "B". Strips with cracks of 1 mm or more and less than 3 mm in length were evaluated as "C". Strips with large cracks of 3 mm or more in length were evaluated as "D".

[0143] In addition, the crack edge length refers to the length of the crack edge from the end portion in the width direction of the rolled material to the center portion in the width direction.

[0144] (tensile strength)

[0145] A No. 13B test piece specified in JIS Z 2201 was collected from the strip for property evaluation, and the tensile strength was measured in accordance with JIS Z 2241.

[0146] In addition, the test piece was collected so that the tensile direction of the tensile test was parallel to the rolling direction of the strip for property evaluation.

[0147] (Electrical conductivity)

[0148] A test piece with a width of 10 mm and a length of 60 mm was collected from the strip for characteristic evaluation, and the resistance was calculated by the four-terminal method. In addition, the size of the test piece was measured using a micrometer, and the volume of the test piece was calculated. Then, the conductivity was calculated from the measured resistance value and volume. In addition, the test piece was collected in a manner that its length direction was parallel to the rolling direction of the strip for characteristic evaluation.

[0149] (Grain size before heat treatment)

[0150] A sample of 20 mm×20 mm was cut out from the obtained strip for property evaluation, and the average crystal grain size was measured by the following method using a SEM-EBSD (Electron Backscatter Diffraction Patterns) measuring device.

[0151] The rolled surface was mechanically polished using water-resistant sandpaper and diamond abrasives. Then, the rolled surface was finely polished using a colloidal silica solution. Afterwards, an electron beam was irradiated at each measuring point (pixel) within the measuring range of the sample surface using a scanning electron microscope. Through the azimuth analysis of backscattered electron diffraction, the measuring points with an azimuth difference of more than 15° between adjacent measuring points were regarded as high-angle grain boundaries, and the measuring points with an azimuth difference of less than 15° between adjacent measuring points were regarded as low-angle grain boundaries. Using the high-angle grain boundaries, a grain boundary map was prepared. Then, according to the cutting method of JIS H0501, for the grain boundary map, 5 line segments of specific length were drawn in the longitudinal and transverse directions at specific intervals. The number of completely cut grains was calculated, and the average value of the cut length was calculated as the grain size before heat treatment.

[0152] (Aspect ratio of grains)

[0153] The aspect ratio of the grains on the rolled surface was measured in the following manner.

[0154] For the rolled surface of the strip for the above-mentioned characteristic evaluation, a grain boundary map was prepared using a SEM-EBSD (Electron Backscatter Diffraction Patterns) measuring device in the same manner as the above-mentioned measurement of the crystal grain size. For the grain boundary map, 5 line segments were drawn along the rolling direction (RD direction) at specific intervals, and 5 line segments were drawn along the direction perpendicular to the rolling direction (width direction, TD direction). The number of completely cut grains was calculated, and the grain size in the RD direction was taken as the major diameter, and the grain size in the TD direction was taken as the minor diameter. In detail, the length of the line segment in the RD direction that was cut by the outline of a grain (the distance between the two intersection points of the line segment and the outline of the grain) was taken as the major diameter of the grain. The length of the line segment in the TD direction that was cut by the outline of a grain was taken as the minor diameter of the grain. The ratio of the major diameter to the minor diameter of each grain (major diameter / minor diameter) was calculated, and the average value was calculated as the aspect ratio.

[0155] (Grain size after heat treatment)

[0156] A test piece was collected from the strip for characteristic evaluation and heat treated at 800°C for 1 hour. A 50 mm × 50 mm sample was cut from the test piece, and the rolled surface was mirror polished and etched. The rolled surface was photographed with an optical microscope in a manner that the rolling direction was transverse to the photograph. The observation area with the finest grains and a size of about 1000 × 1000 μm was selected. 2 The area formed with uniform particle size within the field of view is about 1000×1000μm 2The crystal grains were observed and the crystal grain size was measured. According to the cutting method of JIS H 0501, five line segments of specific length were drawn at specific intervals in the vertical and horizontal directions of the photograph. The number of crystal grains completely cut out was calculated, and the average value of the cut length was calculated as the crystal grain size after heat treatment (average crystal grain size d ave ).

[0157] (Deviation of particle size after heat treatment)

[0158] As described above, samples were collected from the test pieces after the heat treatment, and within the range of 50 mm × 50 mm, excluding twin crystals, the average value of the major and minor diameters of the coarsest grains (i.e., the sum of the major and minor diameters divided by 2) was taken as the maximum grain size d max The coarsest grain is the grain with the largest average value of the long diameter and short diameter in the range of 50mm×50mm. The long diameter is the length of the longest line segment connecting two points on the outline of the grain. The short diameter is the length of the longest line segment cut by the grain boundary (outline of the grain) when a vertical line is drawn on the long diameter. The maximum grain size is compared with the above average grain size d ave The ratio of d max / d ave 10 or less was evaluated as "0" (good), and d max / d ave The case exceeding 10 was evaluated as "×" (poor).

[0159] [Table 1]

[0160]

[0161] [Table 2]

[0162]

[0163] [Table 3]

[0164]

[0165] [Table 4]

[0166]

[0167] [Table 5]

[0168]

[0169] [Table 6]

[0170]

[0171] In Comparative Example 1, since the P content was higher than the range of the present embodiment, the average crystal grain size after heat treatment at 800° C. for 1 hour was coarse at 600 μm, and the variation in grain size was also large.

[0172] In Comparative Examples 2 and 3, since the total content of Pb, Se, and Te is greater than the range of the present embodiment, the variation in grain size after heat treatment at 800° C. for 1 hour becomes large.

[0173] In contrast, in Examples 1 to 37 of the present invention in which the P content was 2 mass ppm or less and the total content of Pb, Se, and Te was 10 mass ppm or less, the average grain size after heat treatment at 800° C. for 1 hour was small and the deviation of the grain size became small. Therefore, the coarsening and inhomogenization of the grains can be suppressed during heating.

[0174] As described above, according to the present examples, it is possible to provide a pure copper plate which is excellent in hot workability and in which coarsening and non-uniformity of crystal grains can be suppressed even after heating.

[0175] Industrial Applicability

[0176] The pure copper plate of this embodiment has excellent hot workability and suppresses the coarsening and inhomogenization of grains after heating. Therefore, the pure copper plate of this embodiment can be preferably used as a substrate for electrical / electronic parts (insulated circuit substrates) such as heat sinks or thick copper circuits, especially electrical / electronic parts for high current applications.

Claims

1. A pure copper plate, characterized in that: The Cu purity is 99.96 mass % or more, the remainder is inevitable impurities, the P content is 2 mass ppm or less, the total content of Pb, Se and Te is 10 mass ppm or less, and the S content is 2 mass ppm or more and 20 mass ppm or less, The grain size of the rolled surface is greater than 40 μm. The aspect ratio of the grains on the rolled surface is less than 2. The maximum grain size d in the area of ​​50 mm × 50 mm after heat treatment at 800°C for 1 hour is max The average crystal grain size d ave The ratio d max / d ave Is below 10.

2. The pure copper plate according to claim 1, characterized in that: The total content of Mg, Sr, Ba, Ti, Zr, Hf, and Y is 10 mass ppm or less.

3. The pure copper plate according to claim 1 or 2, characterized in that: The grain size after heat treatment at 800° C. for 1 hour is within a range of 100 μm to 300 μm.

4. The pure copper plate according to claim 1 or 2, characterized in that: The crystal grain size after being heated at 800° C. or higher and bonded to the ceramic substrate is within a range of 100 μm to 300 μm.

5. The pure copper plate according to claim 1 or 2, characterized in that: The tensile strength is 500 MPa or less.

Citation Information

Patent Citations

  • Crystal grain growth suppressing oxygen free copper

    JP1994002058A

  • Piezoelectric vibration device

    JP2019068304A

  • Hot-rolled copper plate

    CN105189792A

  • Rolled copper foil for flexible PCB and its manufacturing method

    CN1262335A

  • Copper sheet material for copper sheet-provided insulating substrate and production method therefor

    WO2018181593A1